Valorization of spent coffee ground by mixing with various types of residual biomass for pellet production: evaluation of solid biofuel properties at different mixtures - Kougioumtzis, Michael A.; Filippou, Vasileios; Rontogianni, Anatoli; Karampinis, Emmanouil; Grammelis, Panagiotis; Kakaras, Emmanouel (Biofuels, bioproducts and biorefining, 2024)
Coffee consumption is a daily habit for the majority of people worldwide, resulting in consistently large amounts of residue. Spent coffee ground (SCG) is the residue obtained during the brewing process. It represents an abundant source of energy biomass, or raw material for added value products but it is still largely unexploited. This residue may find several applications, such as in polymers/composites precursors, solid/liquid biofuels, biofertilizers, and so forth. The aim of the present paper was the pilot production of pellets by mixing SCG and other residual biomass feedstock. Coffee residues were mixed at different ratios (0, 10, 30, 50, 70, 90 wt%) together with: (i) forestry residues; (ii) sawmill residues; (iii) urban prunings; (iv) maize residues; (v) peach prunings; and (vi) miscanthus. Samples of each fuel mixture were analyzed at the Solid Fuels Laboratory of CPERI/CERTH (Chemical Process and Energy Resources Institute/Centre for Research and Technology Hellas) in Greece by applying established standards. The results of the analyses show that the mixing of biomass residues with coffee could result in competitive solid biofuels. More specifically, pellets with up to 10% coffee residues, mixed with sawmill residues, complied with the class A2 limits set by the international standard ISO 17225‐2 for wood pellets, and pellets with up to 30% coffee residues complied with the class B limits for wood pellets for commercial/residential applications. Urban prunings mixed with 10 wt% coffee residues are within the limits set for class B wood pellets.